Neuroprotective Effect of Brassica oleracea Sprouts Crude Juice in a Cellular Model of Alzheimer's Disease. (9th June 2015) - Masci, Alessandra; Mattioli, Roberto; Costantino, Paolo; Baima, Simona; Morelli, Giorgio; Punzi, Pasqualina; Giordano, Cesare; Pinto, Alessandro; Donini, Lorenzo Maria; d'Erme, Maria; Mosca, Luciana
Abstract : β -Amyloid peptide (A β ) aberrant production and aggregation are major factors implicated in the pathogenesis of Alzheimer's disease (AD), causing neuronal death via oxidative stress. Several studies have highlighted the importance of polyphenolic antioxidant compounds in the treatment of AD, but complex food matrices, characterized by a different relative content of these phytochemicals, have been neglected. In the present study, we analyzed the protective effect on SH-SY5Y cells treated with the fragment A β 25–35 by two crude juices of broccoli sprouts containing different amounts of phenolic compounds as a result of different growth conditions. Both juices protected against A β -induced cytotoxicity and apoptotic cell death as evidenced by cell viability, nuclear chromatin condensation, and apoptotic body formation measurements. These effects were mediated by the modulation of the mitochondrial function and of the HSP70 gene transcription and expression. Furthermore, the juices upregulated the intracellular glutathione content and mRNA levels or activity of antioxidant enzymes such as heme oxygenase-1, thioredoxin, thioredoxin reductase, and NAD(P)H:quinone oxidoreductase 1 via activation of NF-E2-related factor 2 (Nrf2). Although the effects of the two juices were similar, the juice enriched in phenolic compounds showed a greater efficacy in inducing the activation of the Nrf2 signalling pathway.